2011
DOI: 10.1002/ijc.26302
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor kappa B pathway associated biomarkers in AIDS defining malignancies

Abstract: The Nuclear Factor kappa B (NFkB) pathway is essential for many human cancers. Therapeutics such as bortezomib (Velcade™), which interfere with nuclear factor NF-kappa-B(NFkB)signaling are of great clinical interest. NFkB signaling, however, is multifaceted and variable among tissues, developmental, and disease entities. Hence, targeted biomarkers of NFkB pathways are of prime importance for clinical research. We developed a novel real-time qPCR-based NFkB array. Only mechanistically validated NFkB targets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Interestingly, the transcriptomic profile of EBV-positive benign lymphadenophathy was described as closer to BL than to post-transplant lymphoproliferative disease [32], supporting EBV-positive lymphadenopathy as a critical step leading to lymphomagenesis, similar to what we suggest here for C . burnetii infection [32].…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the transcriptomic profile of EBV-positive benign lymphadenophathy was described as closer to BL than to post-transplant lymphoproliferative disease [32], supporting EBV-positive lymphadenopathy as a critical step leading to lymphomagenesis, similar to what we suggest here for C . burnetii infection [32].…”
Section: Discussionsupporting
confidence: 78%
“…In fact, the KS tumor microenvironment is dysregulated and associated with abundant proangiogenic and proinflammatory cytokines (14). High levels of IL-6, TNF-α and IL-10 are present in sera of KS patients whereas IL-1β transcripts are upregulated in KS biopsies (15). …”
Section: Introductionmentioning
confidence: 99%
“…As compared to other herpesvirus polymerase inhibitors, which are purine analogs, AZT is a thymidine analog and appears to be a superior substrate for EBV and KSHV thymidine kinases [11]. Furthermore, we have previously demonstrated that AZT, but not GCV, inhibited nuclear factor κB (NF- κB) activity, thus inducing EBV lytic gene expression and apoptosis in primary type I latency EBV+ BL cell lines [12,13]. The drug methotrexate (MTX) inhibits thymidylate synthase, thus blocking de novo synthesis of dTMP and increasing the likelihood of AZT incorporation into DNA [14].…”
Section: Rationale For the Use Of Zidovudine In Ebv+ Lymphomasmentioning
confidence: 99%